Protective Effects of Casticin From Vitex trifolia Alleviate Eosinophilic Airway Inflammation and Oxidative Stress in a Murine Asthma Model - Liou, Chian-Jiun; Cheng, Ching-Yi; Yeh, Kuo-Wei; Wu, Yi-Hong; Huang, Wen-Chung (Frontiers in Pharmacology, 2018)
Casticin has been isolated from Vitex trifolia and found to have anti-inflammatory and anti-tumor properties. We also previously discovered that casticin can reduce pro-inflammatory cytokines and ICAM-1 expression in inflammatory pulmonary epithelial cells. In the present study, we evaluated whether casticin reduced airway hyper-responsiveness (AHR), airway inflammation, and oxidative stress in the lungs of a murine asthma model and alleviated inflammatory and oxidative responses in tracheal epithelial cells. Female BALB/c mice were randomly divided into five groups: normal controls, ovalbumin (OVA)-induced asthma, and OVA-induced asthma treated with intraperitoneal injection of casticin (5 or 10 mg/kg) or prednisolone (5 mg/kg). Casticin reduced AHR, goblet cell hyperplasia, and oxidative responses in the lungs of mice with asthma. Mechanistic studies revealed that casticin attenuated the levels of Th2 cytokine in bronchoalveolar lavage fluids and regulated the expression of Th2 cytokine and chemokine genes in the lung. Casticin also significantly regulated oxidative stress and reduced inflammation in the lungs of mice with asthma. Consequently, inflammatory tracheal epithelial BEAS-2B cells treated with casticin had significantly suppressed levels of pro-inflammatory cytokines and eotaxin, and reduced THP-1 monocyte cell adherence to BEAS-2B cells via suppressed ICAM-1 expression. Thus, casticin is a powerful immunomodulator, ameliorating pathological changes by suppressing Th2 cytokine expression in mice with asthma.